2003
DOI: 10.1111/j.1399-3089.2004.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of humoral and cellular alloreactivity in baboons sensitized to pig antigens

Abstract: to study whether sensitization to pig antigens results in humoral and/or cellular sensitization to alloantigens in baboons, and thus increases the risks of organ allotransplantation after xenotransplantation. Serum from baboons that were naive (n = 4), sensitized to Gal alpha 1,3Gal (Gal) antigens (n = 2), or sensitized to Gal + non-Gal pig antigens (n = 2) were tested by flow cytometry for the presence of immunoglobulin G (IgG) and IgM antibodies that bind to pig or baboon peripheral blood mononuclear cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…In addition, baboons sensitized to pig antigens did not appear to have a higher sensitization profile towards allogeneic products compared to naïve animals [116]. Taken together, the available information on the relationship between HLA and SLA is not sufficient to enable firm conclusions to be drawn at this stage and further investigations are eagerly awaited to shed some light on the subject.…”
Section: Anti-hla and Anti-sla Antibodiesmentioning
confidence: 96%
“…In addition, baboons sensitized to pig antigens did not appear to have a higher sensitization profile towards allogeneic products compared to naïve animals [116]. Taken together, the available information on the relationship between HLA and SLA is not sufficient to enable firm conclusions to be drawn at this stage and further investigations are eagerly awaited to shed some light on the subject.…”
Section: Anti-hla and Anti-sla Antibodiesmentioning
confidence: 96%
“…It was demonstrated that allosensitization does not increase the risk of antibody-mediated rejection of a GT-KO pig organ, as the extent of human antibody binding and cytotoxicity to GT-KO PBMC did not differ from unsensitized humans [23 ,50 ]. Furthermore, previous studies have indicated that baboons sensitized to pig antigens did not develop antibodies that cross-reacted with baboon alloantigens, offering the opportunity of using a pig organ to act as a 'bridge' until a human organ becomes available [51]. Before xenotransplanatation can proceed to the clinic, however, further life-supporting pig-to-NHP organ transplantation experiments, with a clinically relevant and well tolerated immunosuppressive regimen, will have to show extended graft and recipient survival.…”
Section: The Road To the Clinicmentioning
confidence: 98%
“…71 Later in vitro studies confirmed that, despite the development of high levels of elicited anti-pig Abs, baboons did not develop allosensitization. 72 This would enable a pig organ to be used successfully as a bridge to allotransplantation. 5.…”
Section: The Development Of Ahxr and Tm Can Be Identified By Changes mentioning
confidence: 99%